2021
DOI: 10.1371/journal.pcbi.1008790
|View full text |Cite
|
Sign up to set email alerts
|

Computational epitope map of SARS-CoV-2 spike protein

Abstract: The primary immunological target of COVID-19 vaccines is the SARS-CoV-2 spike (S) protein. S is exposed on the viral surface and mediates viral entry into the host cell. To identify possible antibody binding sites, we performed multi-microsecond molecular dynamics simulations of a 4.1 million atom system containing a patch of viral membrane with four full-length, fully glycosylated and palmitoylated S proteins. By mapping steric accessibility, structural rigidity, sequence conservation, and generic antibody bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(163 citation statements)
references
References 55 publications
9
142
1
Order By: Relevance
“…However, the shorter timescale of these simulations prevented the authors from capturing the opening process at all. With our milliseconds of sampling, we successfully 35,40,41 captured this rare event for both glycosylated and unglycosylated S and found that glycosylation slightly increases the population of the open state, but the difference between glycosylated and unglycosylated S is smaller than that between different spike variants (Supplementary Fig. 1).…”
Section: Extreme Spike Opening Reveals Cryptic Epitopesmentioning
confidence: 97%
“…However, the shorter timescale of these simulations prevented the authors from capturing the opening process at all. With our milliseconds of sampling, we successfully 35,40,41 captured this rare event for both glycosylated and unglycosylated S and found that glycosylation slightly increases the population of the open state, but the difference between glycosylated and unglycosylated S is smaller than that between different spike variants (Supplementary Fig. 1).…”
Section: Extreme Spike Opening Reveals Cryptic Epitopesmentioning
confidence: 97%
“…The structural change of the complexes was easily monitored over simulation trajectories. 37,53,54 The backbone root-meansquare deviation (RMSD) of the complexes suggested that systems mostly reached equilibrium states after 40 ns of MD simulations (Figures S1-S2 of the Supporting Information). Structural analyses were then carried out over equilibrium intervals of S protein + FAb complexes.…”
Section: Resultsmentioning
confidence: 99%
“…played an important role in shaping up our understanding of the dynamics and function of SARS-CoV-2 glycoproteins. [66][67][68][69][70][71][72][73][74][75][76] All-atom MD simulations of the full-length SARS-CoV-2 S glycoprotein embedded in the viral membrane, with a complete glycosylation profile were first reported by Amaro and colleagues, providing the unprecedented level of details and significant structural insights about functional S conformations. 69 A "bottom-up" coarse-grained (CG) model of the SARS-CoV-2 virion integrated data from cryo-EM, x-ray crystallography, and computational predictions to build molecular models of structural SARS-CoV-2 proteins assemble a complete virion model.…”
Section: Computer Simulations and Protein Modelingmentioning
confidence: 99%